THE INFLUENCE OF LOSS LEARNING DURING PANDEMIC OUTBREAK IN ENGLISH ASSESSMENT - Rimba Ayu Sekar Arum; Ahmad Munir; Pratiwi Retnaningdyah (Institut Pendidikan Tapanuli Selatan, 2023)
The pandemic may be declared has over by our president. But the impact of our assessment has left serious problem when student re-entering school to attend sit-in classroom. For two years students and teachers have experienced distance learning during locked-down period. Over many kinds of online platforms, the writer has study the phenomena of result's gap among students specifically in assessing student's English learning. Using qualiative data in finding the result of two research questions, this study has managed to interview an English teacher using score result from student from first semester compared with second semester in 2021. The study has found out that indeed there is tangible loss of this learning process that affect student's score when teacher assessing student's English lesson.